Essays on Saudi oil production, world oil production, and the response of the Saudi macroeconomy to oil shocks - Albaqami, Meznah Hadyan (Kansas State University, 2023)
This three-chapter dissertation examined the effect of Saudi Arabia’s oil supply shocks on non-OPEC and non-Saudi OPEC oil production and the effect of oil price shocks on the Saudi economy. The first chapter predicted how non-OPEC and non-Saudi OPEC oil supplies respond to Saudi oil supply shocks using a Bayesian structural vector autoregression (BSVAR) model on monthly data from 1993 to 2020. The examination of three different prior distributions using prior information found that the response to a Saudi oil shock depends heavily on the identification restrictions. The second chapter also used the BSVAR model to explore whether the CPI response to an oil price shock is offset by Saudi Arabia’s monetary policy. Based on monthly data from 1980 to 2014, the results confirmed that Saudi Arabia’s monetary policy is effective. Following Bernanke et al.’s (1997) methodology, we found that conducting an experiment that reduced the Saudi central bank's response to an oil shock resulted in a much larger response of Saudi inflation to that oil shock. Finally, the third chapter predicts the effect of the structural oil market shocks on sectoral inflation rates in Saudi Arabia using Kilian’s (2009) methodology to help Saudi Arabia’s policymakers overcome inflation rates. As Saudi Arabia’s policymakers seek to overcome the inflation rates, it is useful for them to know how to react in the face of oil market shocks (i.e., the source of oil price increases) to control the inflation rate as sector. The examination found that the effect of oil market shocks on the CPI differs by sector, with oil-specific demand shocks having the largest impact in most sectors compared to other structural oil market shocks.
Keywords: Oil market; Energy economics; Sectoral inflation